The Role of Pre-competitive Sports in achieving Sport Psychological Security among Elite Athletes - amara, noureddine (sports creativity, 2025)
The research problem was, did the pre-competition sport play a role in achieving athletic psychological security among elite athletes ?, The intentional sample was used to collect data, where the Amal Bou Saada team was selected for a second national division (27 players who are constantly active), it has been The descriptive approach was used in this study due to its relevance to the nature of the topic, and the measurement tool was chosen, which is a questionnaire that measures sports psychological security, the study tool was distributed to football players for the Amal Bou Saada club, which is active in the second national division, and the independent study variables are some stage Before sports competition, either Hua's security sports psychological variable, has been relying on the method of analysis and statistical processing in the analysis and processing of results through the Statistical Program for Social Sciences